Proteomic Analysis of Differential Expression of Cellular Proteins in Response to Avian H9N2 Virus Infection of A549 Cells - Yu, Guanliu; Liang, Wei; Liu, Jiyuan; Meng, Dan; Wei, Liangmeng; Chai, Tongjie; Cai, Yumei (Frontiers in Microbiology, 2016)
In this study, differentially expressed proteins in A549 cells (human lung adenocarcinoma epithelial cell line) infected with H9N2 avian influenza virus (AIV) were investigated by two-dimensional electrophoresis (2-DE). Sixteen different spots between the groups (ratio>2, p<0.05) were identified with mass spectrometry identification. Proteins located in the downstream of the NF-κB and IFN transcription factor pathways were identified, e.g. ISG15. Actin and keratin were also identified, which suggesting that the cytoskeleton may plays an important role in the AIV infection of mammalian cells. These findings could provide insights into the interaction between host and influenza viruses and might provide valuable information for clarifying the pathogenesis of viral infections as well.